2021
DOI: 10.1111/are.15616
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, physiological, histopathological, handling, growth and antiparasitic effects of the sodium chloride (salt) in the freshwater fish aquaculture

Abstract: This paper provides the currently available knowledge in the literature regarding the use of sodium chloride (NaCl) in freshwater fish aquaculture and aquaria as related to toxicity, growth performance, transportation, physiology, immunity, histomorphology and antiparasitic treatment. This review assessed and discussed all of these factors, as well as the potential strategies available to be used in fish farming. Acute toxicity to NaCl varies widely among fish species (3.5-150.0 g L −1 ) depending on some envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 140 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…The lethal concentration to kill 50% of individuals (LC 50 ) over 24 to 96 h is the most common laboratory measure of toxicity in fish and contributes to the determination of concentrations and exposure times for in vivo testing (Tavares‐Dias, 2021; Zucker, 1985). The LC 50–96 h values of sodium chloride and trichlorfon for juvenile pirarucu were 9.9 g/L and 9.73 mg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lethal concentration to kill 50% of individuals (LC 50 ) over 24 to 96 h is the most common laboratory measure of toxicity in fish and contributes to the determination of concentrations and exposure times for in vivo testing (Tavares‐Dias, 2021; Zucker, 1985). The LC 50–96 h values of sodium chloride and trichlorfon for juvenile pirarucu were 9.9 g/L and 9.73 mg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sodium chloride, values close to LD 50–96 h (11.88 g/L) were found for the beta fish Betta splendens (Zuanon et al, 2009). The LD 50 values of sodium chloride can vary greatly depending on the exposure time, species, temperature, and other environmental conditions (Tavares‐Dias, 2021). For example, Araújo da Silva et al (2018) found that pirarucu larvae (183.1 ± 41.2 mg; 3.4 ± 0.3 cm) can be reared for 15 days in salinities of up to 4% (4 g/L) with increased fish survival and growth, indicating that A. gigas shows some tolerance to sodium chloride.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some records concerning therapeutic and prophylactic treatments for pirarucu are available, including the use of chemicals applied in therapeutic baths for monogenoid control, i.e., formaldehyde (Andrade-Porto et al 2017) and herbal medicines, such as essential Mentha piperita (Malheiros et al 2016) and Piper aduncum (Corral et al 2018) oils and aqueous P. aduncum extracts (Queiroz et al 2020). In addition, sodium chloride (NaCl), a natural product widely employed in aquaculture activities, has been reported as a promising alternative concerning pirarucu growth and survival, due to its various bene ts and low costs (Silva et al 2019;Tavares-Dias, 2021).…”
Section: Introductionmentioning
confidence: 99%